KORUPSI BIROKRASI PELAYANAN PUBLIK DI ERA OTONOMI DAERAH - Kisno Hadi (Pusat Penelitian Politik, 2010)
Todays big problem in Indonesian state enforcement and governmental system is corruption in both nationaland local level Corruption in public service bureaucracy can only be minimised ifthere is a hollistic and comprehensive understanding within dimension network and background of corruption and some areas in public servicebureaucracy that are highly touched by corruption Without this understanding efforts ofcorruption elimination inpublic service bureaucracy would be hard to achieve In order to support the process ofcorruption elimination inpublic service sector the role ofpublic institutions that is built to control the execution ofpublic service institutionmust be maximised therefore